Seminar Pemuda Berdaulat Undiksha: Menelaah Peran Pemuda dalam Menjaga Kelangsungan Demokrasi - Dea Zailani Lestari; Yuli Tiurida; Putri Siti Nabila; Wahjoe Pangestoeti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Democracy is a system of government based on popular sovereignty, while democratic education is the process of teaching people about democracy, including its concepts, principles, and applications. Every citizen, especially the youth, plays a crucial role in shaping the nation's future. However, the younger generation is often less involved in national political and economic affairs, leading to problems that affect society's quality of life. Government actions often fail to have a positive impact on the younger generation and do not prioritize their interests. Consequently, the younger generation fails to grasp the importance of their role in shaping the nation's future and solving the problems they face. The aim of this activity is to equip the younger generation with modern and peaceful education about democracy. Therefore, it is essential to strive for the role of the younger generation in realizing democracy and economic-political stability so that they can play a more active role and have a positive impact on society.